School insecurity and academic failure in a Mexican public university - Hernández Vázquez, Juan Manuel; Rodríguez Lagunas, Javier; Leyva Piña, Marco Antonio (IE Revista de Investigación Educativa de la REDIECH, 2021)
The objective of this paper is to provide elements to assess the effects of internal as well external insecurity in the academic activity of university students. We explored the cases of the Iztapalapa and Xochimilco campuses of the Universidad Autónoma Metropolitana, located in Mexico City. Physical security is understood as a component of the educational habitability of university spaces, contributing to educational quality. The empirical research was based on a survey applied during the first months of 2018, by sampling the students in the two campuses. Amongst the findings, Iztapalapa appears to have more insecurity issues than Xochimilco; approximately half of the students have been victims of insecurity inside or around the campus, and almost half of them have suffered academic consequences such as missing classes or deserting the institution. The fact that 10% of the students have abandoned their studies due to insecurity could represent an important fact of low terminal efficiency, which is around 50% ten years after admission.